Risk, Resilience and Survival: Migrant Sex Workers on Accra's Oxford Street, Ghana - Sylvester Kyei‐Gyamfi; Frederick Hans Ampiah; Marian Kpakpah (Public Health Challenges, 2026)
ABSTRACT Although female sex workers in Ghana experience multiple occupational risks, limited research has examined how migration status shapes these vulnerabilities and coping strategies. This study investigates the occupational risks and resilience of migrant female sex workers operating along Oxford Street in Osu, Accra, to generate evidence on the distinctive influence of migration on their lived experiences. Guided by the social–ecological model (SEM), a qualitative descriptive design was employed. Twenty migrant female sex workers were recruited using purposive sampling supported by peer referral recruitment and interviewed in English, French or Hausa using a semi‐structured interview guide. The SEM informed the development of the interview guide and the interpretation of the findings, whereas the data were analysed using an inductive thematic approach. Interviews were transcribed verbatim and analysed thematically. Although participants experienced challenges commonly reported among female sex workers, migration status intensified vulnerability through language barriers, deportation threats, xenophobic discrimination, weak access to justice and the absence of family support networks. Participants nevertheless demonstrated resilience through peer solidarity, strategic identity management, spiritual coping and informal safety practices. The study contributes new evidence by demonstrating that migration functions as a structural determinant shaping vulnerability and resilience across multiple ecological levels. The findings underscore the need for migrant‐sensitive, rights‐based and non‐punitive interventions that strengthen protection while recognising migrants’ adaptive survival strategies.